Effect of Horizontal Bandsaw Machine KW15-52 Reconditioning on Vibration and Metal Cutting Time: An Experimental Study - Adian Aristia Anas; Fenoria Putri; M. Fikri (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Horizontal Bandsaw KW15-52 by quantifying changes in vibration and metal cutting time. A quantitative one-group before-and-after experimental design was applied under controlled machining conditions. Thirty paired measurements were obtained for vibration, while 30 cutting trials were conducted for each workpiece material, ST41 steel and Aluminum 6061, before and after reconditioning. The measured outcomes were vibration acceleration (m/s2) and cutting time (s). Reconditioning included inspection, repair or replacement of defective components, reassembly, adjustment, and functional testing. Paired differences were assessed using the Shapiro-Wilk test and paired-samples t-test, with Cohen's dz used to quantify effect size. Vibration decreased from 6.33 ± 0.23 to 3.31 ± 0.41 m/s2, representing a 47.66% reduction, with t = 12.566 and dz = 2.29. Cutting time decreased from 65.77 ± 3.32 to 44.63 ± 3.59 s for ST41 and from 41.13 ± 1.83 to 20.40 ± 1.54 s for Aluminum 6061, corresponding to reductions of 32.1% and 50.4%, respectively. Based on the reported t statistics, all reductions were statistically significant (p < 0.001). The findings demonstrate that systematic reconditioning can substantially restore mechanical stability and cutting efficiency, providing a practical maintenance strategy for extending the service life of mechanical workshop of the Department of Mechanical Engineering, Politeknik Negeri Sriwijaya. Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality Education